Current Development of Electron Beam Irradiation of Natural Rubber–Polymer Blends. Issue 17 (22nd November 2017) - Loo, Kheng-Hooi; Sin, Lee Tin; Bee, Soo-Tueen; Ratnam, C.T.; Tey, Jin-Yuen; Tee, Tiam-Ting; Rahmat, A.R.
ABSTRACT: The application of electron beam irradiation in polymers blend with natural rubber such as thermoplastic polymers, specialty polymers, and thermoset polymers are discussed in this paper for the aspects of physical, mechanical, and thermal properties. The interaction of additives and irradiation for natural rubber blends were also been analyzed. The addition of cross-linking agent such as trimetylolpropane trimethacrylate with appropriate amount could enhance the mechanical properties of the polymer–natural rubber blend and lower the optimum dose of electron beam irradiation. In short, electron beam is another potential aspect worth for study in natural rubber research area. GRAPHICAL ABSTRACT: